2013
DOI: 10.1136/bcr-2013-010410
|View full text |Cite
|
Sign up to set email alerts
|

Human parvovirus B19 associated dilated cardiomyopathy

Abstract: SUMMARYWe describe two children presenting with acute left ventricular dysfunction. Both cases had evidence of dilated cardiomyopathy, requiring inotropic support and were tested for cardiotropic viruses by conventional or real-time polymerase chain reaction using specific primers for enteroviruses, human parvovirus B19, Adenoviruses, Epstein-Barr virus (EBV), herpes simplex viruses 1 and 2 (HSV), human herpes virus-6 (HHV-6) and cytomegalovirus (CMV). IgG and IgM antibodies against parvovirus B19, EBV, HSV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
0
17
0
3
Order By: Relevance
“…Genotype 3 has been reported only sporadically from Asia [Abe et al, ]. The authors have also identified Genotype 3 of B19V from two cases of myocarditis [Jain et al, ]. Until recently, genotype 3 was thought to be restricted to West Africa [Hubschen et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotype 3 has been reported only sporadically from Asia [Abe et al, ]. The authors have also identified Genotype 3 of B19V from two cases of myocarditis [Jain et al, ]. Until recently, genotype 3 was thought to be restricted to West Africa [Hubschen et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that investigators have detected B19V DNA in various percentages of patients with myocarditis (192,853,854), pediatric heart transplant recipients (855), and cases of dilated cardiomyopathy (853,856). The presence of replicative intermediate B19V DNA forms (857)(858)(859) and B19V capsid protein in biopsy specimens has been reported (860), but B19V viral loads have not correlated with outcomes (861). Myositis affecting muscles other than the heart is rarely associated with B19V (798).…”
Section: Clinical Manifestations Diseases Caused By B19v Infectionmentioning
confidence: 99%
“…Genotype 3 was thought to have a restricted distribution, but is recently being reported from various countries, which may be due to improved diagnostic assays or increased spread of the virus [Hubschen et al, ]. The authors have earlier detected genotypes 1 and 3b of B19V in cases of myocarditis [Jain et al, ] and in children with hematological malignancies [Jain et al, ] in North India. The present study detected only genotype 3b of B19V in children receiving chemotherapy for solid tumors at a tertiary care hospital within a defined time period.…”
Section: Discussionmentioning
confidence: 99%